2007
DOI: 10.1080/02813430701241087
|View full text |Cite
|
Sign up to set email alerts
|

Which population groups should be targeted for cardiovascular prevention? A modelling study based on the Norwegian Hordaland Health Study (HUSK)

Abstract: The findings illustrate how choices regarding risk estimation highly affect the size of the target population. Modelling studies are important when preparing guidelines, to address implications for resource allocation and risk of medicalization. The population share to be targeted for primary prevention ought to be estimated, including the impact of various cut-off points for risk algorithms on the size of the risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…This medication pattern reflects that disease burden among older people is dominated by diseases of the cardiovascular and the musculoskeletal system as well as by mental/psychiatric disease. Our results comply with the concepts that most, if not all, of these medication categories increase with age, and women have a higher intake of medications than men (Nielsen et al , ; Brekke et al , Jensen and Schroll, ). The prevalence of polypharmacy was higher in the older age groups, although a trend towards a lower prevalence among the oldest old is in line with observations by Bjerrum et al ().…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This medication pattern reflects that disease burden among older people is dominated by diseases of the cardiovascular and the musculoskeletal system as well as by mental/psychiatric disease. Our results comply with the concepts that most, if not all, of these medication categories increase with age, and women have a higher intake of medications than men (Nielsen et al , ; Brekke et al , Jensen and Schroll, ). The prevalence of polypharmacy was higher in the older age groups, although a trend towards a lower prevalence among the oldest old is in line with observations by Bjerrum et al ().…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with the general concept that diseases of the cardiovascular and the musculoskeletal system are those which most profoundly contribute to the burden of diseases among older people in Denmark as well as in other European countries (Andersen-Ranberg et al, 2001;J€ urges, 2007). Expectedly, we found that the prevalence of diseases/medical conditions were significantly higher in women than in men and most prevalent in the older age groups (Nielsen et al, 2005;Brønnum-Hansen et al, 2006;Iburg et al, 2006;Brekke et al, 2007). The most commonly reported medication groups included anti-thrombotics, cardiovascular agents, antiinflammatory/anti-rheumatics, analgesics and psycholeptics comprising almost 50% of all medications reported.…”
Section: Systemic Diseases/medical Conditions and Medicationssupporting
confidence: 91%
“…(The work of Brekke et al. [31] provides an indication of how the application of different cut‐points can substantially affect the size of the population that is eligible for treatment. )…”
Section: Discussionmentioning
confidence: 99%
“…POWER may offer insights into the usefulness of the SCORE system as a means of focusing necessarily finite resources for optimal effect. (The work of Brekke et al [31] provides an indication of how the application of different cut-points can substantially affect the size of the population that is eligible for treatment. )…”
Section: Discussionmentioning
confidence: 99%
“…This debate should also draw on studies addressing the implications for resource allocation and risk of medicalization and modelling studies estimating the target population for primary prevention of CVD [38,39].…”
Section: Summary Of Principal Findingsmentioning
confidence: 99%